2010
DOI: 10.1051/0004-6361/200912875
|View full text |Cite
|
Sign up to set email alerts
|

The structure of thin accretion discs around magnetised stars

Abstract: Aims. We determine the steady-state of an axisymmetric thin accretion disc with an internal dynamo around a magnetised star. Methods. Starting from the vertically integrated equations of magnetohydrodynamics we derive a single ordinary differential equation for a thin accretion disc around a massive magnetic dipole and integrate this equation numerically from the outside inwards.Results. Our numerical solution shows that the torque between the star and the accretion disc is dominated by the contribution from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The models of Ghosh & Lamb (1979) and Rappaport et al (2004) have ignored the possibility of an internal dynamo in the accretion disc, and have considered only the magnetic field that is generated in the disc by the mismatch in the rotation of the neutron star and the disc. However the magnetic field due to a dynamo can strengthen the coupling between the accretion disc and the neutron star, and we (Tessema & Torkelsson 2010) have shown that the angular momentum exchange between the accretion disc and the neutron star can increase by more than an order of magnitude compared to the standard model by Ghosh & Lamb (1979). Furthermore, the dynamo is insensitive to the rotation of the neutron star, and can therefore in principle provide a spin‐up torque even at a low accretion rate.…”
Section: Introductionmentioning
confidence: 86%
“…The models of Ghosh & Lamb (1979) and Rappaport et al (2004) have ignored the possibility of an internal dynamo in the accretion disc, and have considered only the magnetic field that is generated in the disc by the mismatch in the rotation of the neutron star and the disc. However the magnetic field due to a dynamo can strengthen the coupling between the accretion disc and the neutron star, and we (Tessema & Torkelsson 2010) have shown that the angular momentum exchange between the accretion disc and the neutron star can increase by more than an order of magnitude compared to the standard model by Ghosh & Lamb (1979). Furthermore, the dynamo is insensitive to the rotation of the neutron star, and can therefore in principle provide a spin‐up torque even at a low accretion rate.…”
Section: Introductionmentioning
confidence: 86%
“…The instability has also been invoked as a component of a disc dynamo model, in which the instability creates radial field from vertical field, the shear in the disc creates azimuthal field from the radial component, and the Parker instability creates vertical from azimuthal field and expels flux from the disc [9]. [10] hereafter Paper I, have investigated the interaction between magnetic neutron star and its surrounding accretion disc in the case where the accretion disc is supporting an internal dynamo. They introduced a new solution for an accretion disc around a magnetic star.…”
Section: Introductionmentioning
confidence: 99%
“…Most authors have assumed, like Ghosh & Lamb, that all the angular momentum of the magnetically channelled material is transferred to the star (e.g. Wang 1987; Armitage & Clarke 1996; Matt & Pudritz 2005; Tessema & Torkelsson 2010; Campbell 2011). However, Shu et al (1994a,b) and Ostriker & Shu (1995) developed a modified model of the star–disc interaction in which the accretion torque on the star is greatly reduced.…”
Section: Introductionmentioning
confidence: 99%